2021
DOI: 10.3390/nu13041071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Christian Orthodox Fasting Versus Time-Restricted Eating on Plasma Irisin Concentrations Among Overweight Metabolically Healthy Individuals

Abstract: Irisin has been recently identified as an adipomyokine produced during physical activity and involved in the browning of adipose tissue. Despite the emerging evidence suggesting an inverse relationship between irisin plasma concentrations and adverse metabolic outcomes, the exact impact of diet on irisin levels remains obscure. Thus, we aimed to assess the effects of two dietary patterns, Christian Orthodox fasting (OF) and 16:8 time-restricted eating (TRE), on circulating irisin levels among overweight, metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Other recent studies showed the beneficial effect of COC fasting on metabolic health indices ( 148 , 149 , 158 ). For example, it has been shown that COC fasting has superior lipid-lowering effects compared to the TRE pattern in overweight adults ( 148 ).…”
Section: Greek Orthodox Christian Fastingmentioning
confidence: 84%
See 1 more Smart Citation
“…Other recent studies showed the beneficial effect of COC fasting on metabolic health indices ( 148 , 149 , 158 ). For example, it has been shown that COC fasting has superior lipid-lowering effects compared to the TRE pattern in overweight adults ( 148 ).…”
Section: Greek Orthodox Christian Fastingmentioning
confidence: 84%
“…For example, it has been shown that COC fasting has superior lipid-lowering effects compared to the TRE pattern in overweight adults ( 148 ). In addition, the favorable long-term effects of COC on irisin levels (involved in the adipose tissue browning) in overweight, metabolically healthy, adults have been shown ( 158 ).…”
Section: Greek Orthodox Christian Fastingmentioning
confidence: 99%
“…Future randomized studies are needed to eliminate the bias of the self-selection of fasting as an intervention. Randomization is truly unfeasible in studies investigating religious types of fasting [ 47 ]; nonetheless, more rigorous research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether it is NAFLD itself or its comorbidities such as obesity or diabetes that affects circulating irisin, while most of the included studies failed to control for such factors when making comparisons. Moreover, data on lifestyle factors such as physical activity and nutrient intake were not well reported, which may also influence the comparison of irisin levels in NAFLD versus controls [8,36,37]. Third, although irisin has been proven to exist [38], the accuracy of the ELISA kits used for its detection remains unclear and needs to be validated against mass spectrometry [39,40].…”
Section: Strengths and Limitationsmentioning
confidence: 99%